2009
DOI: 10.1002/aic.11771
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of the flow field in a RIM machine mixing chamber

Abstract: Dynamic behavior of the flow field in a Reaction Injection Molding, RIM, machine mixing chamber, having dimensions typically used in industrial machines, is studied from dynamic velocity data of Laser Doppler Anemometry, LDA, measurements and Computational Fluid Dynamics, CFD, simulations with a 2D model. This study is based on the spectral analysis of the dynamic flow field data. The typical frequencies, in the reactor flow field, are identified and its values are related to the identified flow structures. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 18 publications
(41 reference statements)
4
73
0
Order By: Relevance
“…The dynamic behavior of the flow field in RIM has been well studied at Re \ 600. [8][9][10][11][12] The similar conclusion of these studies is that there exists a critical Re % 90, above which occurs the flow-field transition from stable laminar to unstable oscillation. The flow visualization in RIM shows that the impingement interface is distorted and displays a sustainable chaotic flow regime by the vortices formed near the impingement point as Re is larger than the critical one.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…The dynamic behavior of the flow field in RIM has been well studied at Re \ 600. [8][9][10][11][12] The similar conclusion of these studies is that there exists a critical Re % 90, above which occurs the flow-field transition from stable laminar to unstable oscillation. The flow visualization in RIM shows that the impingement interface is distorted and displays a sustainable chaotic flow regime by the vortices formed near the impingement point as Re is larger than the critical one.…”
Section: Introductionsupporting
confidence: 64%
“…The flow visualization in RIM shows that the impingement interface is distorted and displays a sustainable chaotic flow regime by the vortices formed near the impingement point as Re is larger than the critical one. 11,12 Stan and Johnson have studied two axisymmetric turbulent opposed water jets in a tank and found that there was an irregular low frequency oscillation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) for the impingement plane along the symmetric axis. 16 In the experiment of Denshchikov et al, oscillation of two opposed planar water jets at 100 \ Re \ 4800 was also observed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It must be pointed out first that the self-sustained chaotic oscillation in RIM is related to the confined boundary condition, [15][16][17][18][19] which is different to the low-frequency periodic oscillation of axisymmetric opposed jets with excitations. Second, current results can be used to explain the low-frequency irregular oscillations reported in the experiments 20,21 but absent in the simulation and stability analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] At 250 < Re < 600, the flow in RIM shows a self-sustained chaotic oscillation, and its St is about 0.04 and is found to be determined by the geometry configuration of mixing chamber. 18,19 However, Stan and Johnson 20 have observed an irregular lowfrequency oscillation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) for two opposed water jets, and the corresponding values of St are in the range of 2-8. In our previous study, 21 we have also observed some axial irregular oscillations or quasiperiodic oscillations for unrestricted axisymmetric opposed jets occasionally, whose peak frequency is about 10 Hz and St is in the range of 0.01-0.07.…”
Section: Introductionmentioning
confidence: 94%